Training on the Implementation of Storytelling Learning with the Animation Film Method for PAUD Teachers in Bontoa Maros District - Nurhayati; Inriati Lewa; Mulimat; Muh. Akdan; Indarwati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
This Community Service is entitled Training on the Implementation of Storytelling Learning using the Animation Film Method for FAUD Teachers throughout the Bontoa Maros District. This topic was chosen based on the results of an interview with a teacher in Bonto Maros, South Sulawesi, that PAUD teachers in that area really need this material because they don't know what literature, children's literature, and the method of telling stories through animated films are. The importance of this material is given because so far PAUD teachers in the area still use conventional methods in teaching fairy tales. The method used in this service is training and practice. During the training, teachers were given learning materials for literature in general, children's literature, and learning methods using the animated film method. The results achieved were that PAUD teachers got the material and would apply it in class. The importance of this training for PAUD teachers throughout the Bontoa District considering that they are still using conventional methods. The teachers were satisfied and asked if it was possible to add more time to the material.